2019
DOI: 10.1093/ve/vez044
|View full text |Cite
|
Sign up to set email alerts
|

A non-parametric analytic framework for within-host viral phylogenies and a test for HIV-1 founder multiplicity

Abstract: Phylogenetics is a powerful tool for understanding the diversification dynamics of viral pathogens. Here we present an extension of the spectral density profile of the modified graph Laplacian, which facilitates the characterization of within-host molecular evolution of viruses and the direct comparison of diversification dynamics between hosts. This approach is non-parametric and therefore fast and model-free. We used simulations of within-host evolutionary scenarios to evaluate the efficiency of our approach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

5
2

Authors

Journals

citations
Cited by 16 publications
(28 citation statements)
references
References 58 publications
1
27
0
Order By: Relevance
“…S9 and S10 ) ( 33 35 ). We estimated phylogenetic η ( 36 , 37 ) at each internal node of the SARS-CoV-2 phylogeny reconstructed from subsampled (10%) alignments and compared the distribution of estimates through time to phylogenies simulated under models of neutral and positive time-dependent rates (b(t) = be α(t) ). Simulation analyses demonstrated that this metric was robust against sampling fraction ( SI Appendix , Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…S9 and S10 ) ( 33 35 ). We estimated phylogenetic η ( 36 , 37 ) at each internal node of the SARS-CoV-2 phylogeny reconstructed from subsampled (10%) alignments and compared the distribution of estimates through time to phylogenies simulated under models of neutral and positive time-dependent rates (b(t) = be α(t) ). Simulation analyses demonstrated that this metric was robust against sampling fraction ( SI Appendix , Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Time-dependent estimates of phylogenetic diversification were measured by extracting the branches descending from each internal node (above the root) of each phylogeny and calculating the peak height (η) of the spectral density profile of the graph Laplacian of each subtree, which is a measure of the density of branching events ( 36 , 37 ). The code to perform the analysis is available for download at https://www.hivresearch.org/publication-supplements .…”
Section: Methodsmentioning
confidence: 99%
“…Using qualitative (e.g., tree topologies) and quantitative (e.g., intra-host maximum diversity) measures of sequence diversity as previously described [21,[34][35][36][37], we could distinguish two subgroups in our cohort: most participants (28/39) were infected with single HIV-1 founders whereas eleven participants (28%) had multiple HIV-1 founders. To detect infections with multiple founders, we also analyzed spectral density profiles derived from each participant's maximum-likelihood phylogeny [38] [39]. We evaluated founder multiplicity based on the principal eigenvalue test, performed on the eigenvalues calculated from the weighted graph Laplacian of the distance matrix of the phylogeny for each participant (S2 Fig).…”
Section: Hiv-1 Genomes From the First Days Of Hiv-1 Infectionmentioning
confidence: 99%
“…The profiles of eigenvalues for each participant were clustered based on Jensen-Shannon distances [65] using an unbiased hierarchical approach with bootstrap probabilities calculated at each node. We then evaluated the founder multiplicity of each participant based on the principal eigenvalue test [38,39], where the threshold between single and multiple founders was determined by the median criterion (the median principal eigenvalue plus 0.5 x standard deviation squared), the jump criterion (the position of the largest discrepancy between consecutive ranked principal eigenvalues), and the partition criterion (clustering on the principal eigenvalue by partitioning around medoids [66]). Finally, we estimated the spectral density profile summary statistics for each participant: principal eigenvalue (lambda � ), the skewness of the profile (psi), and the peak height of the profile (eta).…”
Section: Identification Of Infections With Multiple Hiv-1 Foundersmentioning
confidence: 99%
“…25 It is particularly unclear in this scenario how to distinguish closely-related founder variants that diverged in the donor population from stochastic early mutations separating variants that diverged in the recipient population. A variety of founder identification methods of varying complexity exist, [26][27][28] and do not uniformly agree. Both APOBEC and multivariant transmission are examples of processes that inflate the average pairwise distance be- tween sequences and cause violations of the Poisson assumptions that Poisson-Fitter relies upon.…”
Section: Introductionmentioning
confidence: 99%